“Aplicación de cuatro dosis de materia orgánica (pollaza) en el rendimiento de grano seco del frijol trepador (phaseolus vulgaris) variedad huasca poroto en el distrito de Lamas” - Mejía Camones, Janett Catalina (2015)
This research aimed to study and determine which of the four doses of pollaza has greater effect on yield and economic benefit in dry grain growing climbing beans (Phaseolus vulgaris) Bean variety Huasca The Huallaga, under the system trellis in the district of Lamas. The research was conducted on the grounds of the Fundo "The Pacific" owned by Mr. Jorge Luis Pelaez Rivera, politically located in the district and province of Lamas, San Martín department. The statistical design of randomized complete block (RCBD) with four replications and five treatments, with a total of 20 experimental units was used. The information gathered in the field was processed using SPSS 19 statistical software, which uses the P-value as meaningful comparison to the confidence levels of 0.05 and 0.01 differences in the analysis of variance (ANVA) and multiple range test of Duncan P s 0.05. The treatments were: TO: (control), T1 (10 pollaza t.ha-1), T2 (20 pollaza t.ha-1), T3 (30 pollaza t.ha-1 ), T4 (40 pollaza t.ha-1). The variables evaluated were: emergency percentage, plant height, number of pods per plant, number of seeds per pod, grain weight, yield and economic analysis. The results indicate that treated with the dose of 40 t ha-1 pollaza, plants proved to be the most appropriate treatment, determinad to influence the biggest and best performance increase with 24358.26 kg ha-1 , generating a profit I cost of 2.01 anda net profit of S /. 11394.95 new soles, respectively. Keywords: Culture, beans, bean huasca, dose, performance, profit, pollaza effect.